Kepuasan Kerja Ditinjau Dari Kualitas Kehidupan Kerja dan Budaya Organisasi - Despiana, Dwi; Almas Zakiyyah, Nabila (Jurnal Ilmiah Psyche, 2025)
Attention to working conditions and internal dynamics has become an essential aspect as employees increasingly demand positive working conditions and facilitate employee development. Companies need to ensure that workers not only receive adequate facilities but also experience positive values, norms, and patterns of interaction in their daily work routines. Quality of work life and organizational culture play important roles in enhancing employee job satisfaction. This study aims to determine the extent to which these two factors influence job satisfaction levels. The research subjects consisted of 152 employees of PT Mars Lestari Palembang, selected using a simple random sampling method. Data were collected using several scales: a quality of work life scale containing 41 items, an organizational culture scale with 25 items, and a job satisfaction scale with 33 items. The analysis results showed that the coefficient of determination (R Square) was 0.664 with a significance value of 0.00 (p < 0.05). These findings indicate that quality of work life and organizational culture significantly affect employee job satisfaction.